Materiomics: a toolkit for developing new biomaterials - Hook, Andrew; Morgan, Alexander; Winkler, David A. (Elsevier, 2015)
Learning Objectives • To understand the what materiomics is and why it is required • To become familiar with the various approaches used to design materiomic experiments • To learn what a polymer microarray is, what it is used for and how it is produced • To appreciate the complexity of material-biological interactions • To become familiar with computational modelling methods as applied to biomaterials • To gain an insight into how materiomics has and will continue to benefit tissue engineering